Liebling's war World War II dispatches of A.J. Liebling - Liebling, A. J. (Abbott Joseph), 1904-1963.; Barbour, James 1933-; Scharnhorst, Gary; Warner, Fred (Albuquerque : University of New Mexico Press, 2010)
"The New Yorker sent [A.J.] Liebling to Paris in October 1939 to cover the war in Europe. The assignment lasted through the liberation of Paris and a few weeks thereafter, and here for the first time Liebling's war dispatches ... are arranged to form a coherent narrative"--Jacket.
Part I: 1939-1940. Toward Paris : 1939 ; Merry Christmas, Horrid New Year ; Colonel Albatross ; Letter from Paris, 14 April 1940 ; Letter from Paris, 21 April 1940 ; The knockdown ; Letter from Paris, 24 May 1940 ; Letter from Paris, 1 June 1940 ; Who do not fight, but run away ; A man falling downstairs -- Part II: 1940-1942. No place like it ; Rape is impossible ; It showed nice instincts ; Dev's double ; Westbound tanker -- Part III: 1942-1943. Toward a happy ending ; Birds of my country ; The foamy fields ; Gafsa ; Under the acacias -- Part IV: 1943-1944. Quest for Mollie ; Cross-channel trip ; Letter from France, 14 July 1944 ; Letter from France, 20 July 1944 ; Letter from France, 4 August 1944 ; Letter from Paris, 1 September 1944 -- Part V: 1955-1958. Tickey-boo on Easy Red ; Days with the Daydaybay ; The navel of the Loire.
105052
Keywords: Liebling, A. J. -- 1904-1963 -- Correspondence; 1939 - 1945; World War, 1939-1945 -- Personal narratives, American; War correspondents -- United States -- Correspondence; War correspondents -- France -- Correspondence; World War, 1939-1945 -- France -- Paris; World War, 1939-1945 -- Campaigns -- France -- Normandy; Military campaigns; Travel; War correspondents; Paris (France) -- History -- 1940-1944.; Paris (France) -- Description and travel; Normandy (France) -- Description and travel; France; France -- Normandy; France -- Paris; United States; History; Personal narratives -- American; Records and correspondence